INNOVATION IN BUSINESS FINANCING - Sultanova Lola Sharafovna; Karimov Diyor Mukhtarovich (Journals Park Publishing, 2022)
The article considers approaches to solving the problems of financing new fast-growing firms through innovative investment instruments.
Keywords: crowdfunding, crowdsourcing, venture investors, business angels business accelerators, business incubators.